Novel protocol to establish the myocardial infarction model in rats using a combination of medetomidine-midazolam-butorphanol (MMB) and atipamezole - Farag, Ahmed; Mandour, Ahmed S.; Hamabe, Lina; Yoshida, Tomohiko; Shimada, Kazumi; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background Myocardial infarction (MI) is one of the most common cardiac problems causing deaths in humans. Previously validated anesthetic agents used in MI model establishment are currently controversial with severe restrictions because of ethical concerns. The combination between medetomidine, midazolam, and butorphanol (MMB) is commonly used in different animal models. The possibility of MMB combination to establish the MI model in rats did not study yet which is difficult because of severe respiratory depression and delayed recovery post-surgery, resulting in significant deaths. Atipamezole is used to counter the cardiopulmonary suppressive effect of MMB. Objectives The aim of the present study is to establish MI model in rats using a novel anesthetic combination between MMB and Atipamezole. Materials and methods Twenty-five Sprague Dawley (SD) rats were included. Rats were prepared for induction of the Myocardial infarction (MI) model through thoracotomy. Anesthesia was initially induced with a mixture of MMB (0.3/5.0/5.0 mg/kg/SC), respectively. After endotracheal intubation, rats were maintained with isoflurane 1% which gradually reduced after chest closing. MI was induced through the left anterior descending (LAD) artery ligation technique. Atipamezole was administered after finishing all surgical procedures at a dose rate of 1.0 mg/kg/SC. Cardiac function parameters were evaluated using ECG (before and after atipamezole administration) and transthoracic echocardiography (before and 1 month after MI induction) to confirm the successful model. The induction time, operation time, and recovery time were calculated. The success rate of the MI model was also calculated. Results MI was successfully established with the mentioned anesthetic protocol through the LAD ligation technique and confirmed through changes in ECG and echocardiographic parameters after MI. ECG data was improved after atipamezole administration through a significant increase in heart rate (HR), PR Interval, QRS Interval, and QT correction (QTc) and a significant reduction in RR Interval. Atipamezole enables rats to recover voluntary respiratory movement (VRM), wakefulness, movement, and posture within a very short time after administration. Echocardiographic ally, MI rats showed a significant decrease in the left ventricular wall thickness, EF, FS, and increased left ventricular diastolic and systolic internal diameter. In addition, induction time (3.440 ± 1.044), operation time (29.40 ± 3.663), partial recovery time (10.84 ± 3.313), and complete recovery time (12.36 ± 4.847) were relatively short. Moreover, the success rate of the anesthetic protocol was 100%, and all rats were maintained for 1 month after surgery with a survival rate of 88%. Conclusion Our protocol produced a more easy anesthetic effect and time-saving procedures with a highly successful rate in MI rats. Subcutaneous injection of Atipamezole efficiently counters the cardiopulmonary side effect of MMB which is necessary for rapid recovery and subsequently enhancing the survival rate during the creation of the MI model in rats.